The electronics handbook - Whitaker, Jerry C (Electrical engineering handbook series., 1996)
Provides basic information on the theory and principles that govern electronic devices and systems. The text also presents proven techniques and methods, working guidelines, and advice on a wide range of topics related to modern electronics.